2013
DOI: 10.1259/bjr.20130253
|View full text |Cite
|
Sign up to set email alerts
|

Multiplanar 3D ultrasound imaging to assess the anatomy of the upper airway and measure the subglottic and tracheal diameters in adults

Abstract: This is the first report to describe the use of 3D ultrasound to evaluate the anatomy of the upper airway and accurately measure the AP diameter of the subglottic space and the transverse diameter of the upper trachea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
(15 reference statements)
0
19
0
Order By: Relevance
“…Overall trends demonstrate the increasing use of cross-sectional imaging of the neck [15]. Ultrasound technology has been previously utilized to demonstrate the structural anatomy of the upper airway and trachea [16] with good correlation observed when compared with MRI-derived soft tissue anatomy [17].…”
Section: Resultsmentioning
confidence: 98%
“…Overall trends demonstrate the increasing use of cross-sectional imaging of the neck [15]. Ultrasound technology has been previously utilized to demonstrate the structural anatomy of the upper airway and trachea [16] with good correlation observed when compared with MRI-derived soft tissue anatomy [17].…”
Section: Resultsmentioning
confidence: 98%
“…Lakhal et al 8 reported a good correlation between ultrasound and MRI measurements of the transverse diameter of the cricoid cartilage, and that ultrasound could accurately measure the transverse diameter of the subglottic space. However, Or DYL et al 11 found that, compared with the MRI results, ultrasound overestimated the transverse diameter of the subglottic space.…”
Section: Discussionmentioning
confidence: 94%
“…Size is generally selected by age‐based formulas, which in turn are based on morphometric data of the tracheal dimensions and the effective functional area needed by a child for breathing. The methods of tracheal measurement have included cadaver measurement, chest radiograph, ultrasound, magnetic resonance imaging (MRI), and CT scan . However, most of the measurement data are based on Western literature, with very few Asian studies .…”
Section: Discussionmentioning
confidence: 99%